Effect of Financial Knowledge and Locus Of Control on Personal Financial Management Behavior with Financial Literacy as Mediator Variable - Syafrina Syafrina; Abel Tasman (Financial Management Studies, 2022)
This study aims to analyze the effect of: (1) Financial Knowledge and (2) Internal Locus of Control on Personal Financial Management Behavior with Financial Literacy as a Mediator Variable. The population used is all students of Generation Z Strata 1 who are actively studying at Padang State University, amounting to 31,553 people. The sampling technique of this study used the Cluster Random Sampling technique with a total sample of 335 people. This study uses primary data and secondary data. The data analysis method used is Structural Equation Modeling (SEM) using SmartPLS version 3.3. The results of this study show that (1) Financial Knowledge and Internal Locus of Control have a positive and significant effect on Financial Literacy (2) Financial Knowledge and Internal Locus of Control have a positive and significant effect on Personal Financial Management Behavior (3) Financial Literacy has a positive and significant effect on significant effect on Personal Financial Management Behavior (4) Financial Knowledge and Internal Locus of Control have a positive and significant effect on Personal Financial Management Behavior with Financial Literacy as a Mediator Variable, in Generation Z students at Padang State University.